Agents of S.U.I.T : sew much trouble - Green, John Patrick, 1975-; Hastings, Chris, 1983- (Green, John Patrick, 1975- InvestiGators. Agents of S.U.I.T., 2026)
"Someone has stolen the Notorious P.I.G. food truck, and with it,Piggy Smalls's special BBQ sauce! But before Bongo and Marsha can solve the case, they need to solve the problems they're having with each other. To help them realize what a great team they truly are, General Inspector decides to split them up. He assigns Marsha to work with Cilantro on a super-secret pilot program, and Bongo to work with Sven on a not so-secret reality competition: "Sew You Think You Can Sew!" But here's the rub: This season includes a chef challenge, and underground sources say Piggy Smalls's notorious sauce was stolento help one of the contestants win!"--